Understanding The Everyday Digital Lives of Children and Young People - Folkvord, Maren Svendsen (Nordic Journal of Comparative and International Education (NJCIE), 2025)
“Understanding The Everyday Digital Lives of Children and Young People”, edited by Halla Holmarsdottir, Idunn Seland, Christer Hyggen and Maria Roth is an exploration of the impact of technological transformations on children and young people aged 5-18 years, referred to as the Digital Generation. This book is a useful and important contribution to increasing our insight into children and young people's digital everyday lives today, in a holistic and curious way, as it goes beyond the technological determinism implicit in studies that repeatedly find small correlations between online activity and adolescent well-being. The book is also an important starting point for further research on children and young people and can especially be of inspiration regarding the use of various creative methods that involve children and young people in research, to bring out the young people's own perspectives, understandings, thoughts, feelings and practices.